Analysis of Factors Affecting the Implementation of “Remaja Sehat” Application - Riris Diana R1, Pulung Siswantara1, Muthmainnah1 , Astri Meidah Setiawati1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aims to determine the effect of relative profitability, compatibility, complexity, trialability, and observability about knowledge regarding adolescent reproductive health in the use of the “Remaja Sehat” application. Implementation of the use of the media “Aplikasi Remaja Sehat” was carried out by 302 students of SMAN 19 Surabaya and SMA Muhammadiyah 7 Surabaya. Effectiveness measurement used pre-experiment methods with post-only design. The results of this study showed that there are relative advantages (0.013) and trialability (0.000) have an effect while compatibility (0.666), complexity (0.464) and observability (0.281) have no effect on the implementation of the use of “Remaja Sehat” application.